KORELASI ANTARA DERAJAT GASTRITIS DAN RASIO PEPSINOGEN I/II PADA PENDERITA GASTRITIS KRONIS - Dary, I Wayan; Wibawa, I Dewa Nyoman (journal of internal medicine, 2009)
Chronic gastritis is a histopathological entity characterized by chronic inflammation of the stomach mucosa. Chronicgastritis tend to damage stomach mucosa and be atrophy sequence to change gastric physiology. Pepsinogen (PG) can be used asÔserologic biopsy,Õ as clinical application for evaluating gastric inflammations. The different cellular origins of PG I and PG II areimportant because alteration in their serum concentration can be correlated with some histological gastric anomalies. To determinethe correlation between grade of gastritis and PG I/II ratio (PGR) in chronic gastritis patients, we conducted an analyticcross sectional study in 64 gastritis patients whom enrolled consecutively. Gastric mucosal of dyspeptic patients who had uppergastrointestinal endoscopy biopsy 2 at anthrum and 2 at corpus were examined histologically using the Updated Sydney System(USS) by two pathologists independently, and also the serum examined for PG I, PG II, and IgG H. pylori. Degree of gastritis wascounted with the USS method. Pepsinogen examination used ELISA method, however IgG H. pylori examanition usedimmunochromatographic test (ICT) method with local reagen. H. pylori positive if serologically H. pylori positive and or histologicallyH. pylori positive. Interobserver agreement for histopatology abnormalities were examined by using kappa test. Thedifference PGR and severity of gastritis between subjectswith H. pylori positive and H. pylori negative were identified by usingMann-Whitney U test. Correlation between the severity of gastritis and PGR was identified by using spearmanÕs test and theeffect of total USS score and H. pylori to PGR was identified by using dummy regression, also to know the effect of PGR and H.pylorito total USS score was identified by using dummy regression. Pvalue of less than 0.05 was considered statistically significant.There were 64 chronic gastritis whom mean age 45.9 ± 15.5 year, consisted of 44 male and 20 female. The level of PG I218.70 (53,90 Ð 530.00) mg/L, PG II 15.72 (2.84 Ð 59.25) mg/L, dan PGR 12.66 (28.97 Ð 5.80). Interobserver agreement of gastrichistologic examanation shown moderate to substantial criteria (k = 0.590 Ð 0.795) with polymorphonuclear activity k = 0.795,glandular atrophy k = 0.591, density of H. pylori k = 0.727, chronic inflammation k = 0.629, and intestinal metaplasia k = 0.778.The frequency of abnormalities gastric mucosa as infected H. pylori 28.1%, inflammation 100.0%, polymorphonuclear activity22.8%, atrophy 37.5%, and intestinal metaplasia 6.2%. Total USS score from 1 to 9 and most of them had score 1 and 2 withfrequency 17 (26,6%) and 15 (24,4%) respectively. Subjects with H. pyloriinfection had lower PGR than uninfected subjects(11.2 ± 4.3 mg/L vs 15.0 ± 5.1 mg/L, p = 0.001; Mann-Whitney U test), and also subjects with H. pyloriinfection had higherseverity of gastritis than uninfected subjects either degree of inflammation, activity polymorphonuclear, and atrophy (p = 0.000,p = 0.004, p = 0.041 respectively; Mann-Whitney Utest). There was significant inversed correlation between total USS score andPGR (r = -0.470, p < 0.0001; SpearmanÕs tes). Significant effect of total USS score and positivity H. pylori to PGR (F = 7.015, p = 0.002; dummy regression), but only coefficient of total USS score significantly (t = -2.030, p = 0.047), however positvity H.pylori didnÕt influence PGR significatly (t = -1.199, p = 0.235). Total USS score influences PGR as much as 15,4% (adjusted R2= 0.154, F = 12.504, p = 0.001; linier regression) with regression coefficient -0,933 (t = -3.536, p = 0.001). H. pylori serology andPGR can be used to determine total USS score significantly (F = 9.498, p < 0.0001; dummy regression) and both of regressioncoefficient were significant (t = -3.417, p = 0.001; t = 2.360, p = 0.021 respectively; dummy regression) how ever can be madeÔserologic biopsyÕ with formula Ôtotal USS score = 6.786-0.169.PGRÕ for H. pylori positive subjects and Ôtotal USS score = 5.258Ð 0.169.PGRÕ for H. pylori negative subjects. In conclusion that there was a significant inversed correlation between total USSscore and PGR, formula Ôserologic biopsyÕ to determine total USS score were Ôtotal USS score = 6.786 Ð 0.169.PGRÕ for H. pyloripositive subjects and Ôtotal USS score = 5.258 Ð 0.169.PGRÕ for H. pylori negative subjects.